2021
DOI: 10.3126/jfac.v3i1.42489
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of educational virtual class during Covid-19- with reference of Music online class of Fine Arts Campus, TU

Abstract: As the Covid19 pandemic started, COVID infected nations announced to keep physical distance, affected all the human activities, as a result, educational institutions closed physically. The aim of the present research was to study the effectiveness of virtual class during Covid-19 with reference to music online class of Fine Arts Campus, TU. An online survey design was used by taking responses of 47 students of the Bachelors' program and further corresponded with 16 teachers, and 17 parents for the data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Material centered method like audio-visual guidance (Leow & Neo, 2014), musical concerts and performances would be beneficial for the students. The respondents also argued that the novel and digital pedagogical practices are not applicable in the university because of low investment, lack of training, lack of infrastructure and resources, and unclear policy of the university, a recent case study also concluded alike (Poudel, 2021). Besides that, the university should free from politics and those teachers having good performance, regular, better outcomes of the students and dedicated to their job should be awarded whereas Fisher et al (1981) and Open Access Schoenfeld (1988) also argued with these arguments.…”
Section: Figure 1 Views Of Academicians Towards Curriculum Perception...mentioning
confidence: 99%
“…Material centered method like audio-visual guidance (Leow & Neo, 2014), musical concerts and performances would be beneficial for the students. The respondents also argued that the novel and digital pedagogical practices are not applicable in the university because of low investment, lack of training, lack of infrastructure and resources, and unclear policy of the university, a recent case study also concluded alike (Poudel, 2021). Besides that, the university should free from politics and those teachers having good performance, regular, better outcomes of the students and dedicated to their job should be awarded whereas Fisher et al (1981) and Open Access Schoenfeld (1988) also argued with these arguments.…”
Section: Figure 1 Views Of Academicians Towards Curriculum Perception...mentioning
confidence: 99%
“…To achieve the goal of teaching and learning, teacher faces numerous obstacles. For teachers who have been doing classroom instruction for a long time, teaching online is a massive challenge in and of itself, as per a study by Poudel (2021). Additionally, various studies conclude that most developing countries of the world like Nepal, their educational institutions and teacher faces challenging for teaching math online.…”
Section: Introductionmentioning
confidence: 99%